(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Healthcare-associated infections are still a significant concern for healthcare workers (HCWs). This is because the risk of exposure to blood and body fluids is high during their work. Infection control is a challenge for every healthcare setting. Universal precautions are essential in infection control. They protect healthcare providers and prevent the spread of infection from patient to patient as well. Aim: To determine the level of knowledge and practice of universal precautions among healthcare workers. Materials and methods: The study used a descriptive research design. Ethical clearance was obtained from an institutional ethics committee, permission was obtained from the concerned authority and informed consent was taken from the study participants. Using a nonprobability convenient sampling technique100 study participants were selected. Data was collected using a structured knowledge questionnaire and structured self-reported practice checklist. The data were analyzed using descriptive and inferential statistics. Results: The majority (75%) of the study participants belong to the age group of 22-26, the majority (70%) were females, and the majority (32%) were nurses. The mean knowledge score was 19.11±2.63. The majority (62%) of the study participants had good knowledge and 38% had excellent knowledge regarding universal precautions. The mean practice score was 66.02±6.14. All the study participants showed having good practice of universal precautions. The study found a positive correlation between knowledge and practice (r=0.29) of healthcare workers. Conclusion: The study concluded that the majority of the healthcare workers had good knowledge and all had good practices towards universal precautions.